Periodontology as a recognized dental speciality in Europe - Mariano Sanz (journal of clinical periodontology, 2006)
The impetus of the Bologna Process under the auspices of European Union governments has raised enormous expectations. It is the major educational change in Europe within the last 50 years and all the focus from university institutions, learned societies and thematic networks has shifted to this process, with the aim of developing consensus schemes in order to arrive at the expected European Convergence in Higher Education (to be completed by 2010). Dentistry as one of the health professions with clear Educational Standards, as defined by the European Dental Directives, is also reviewing its educational processes within this Bachelor–Master–Doctorate scheme and evaluating how the current and future dental specialities should be accommodated within this framework. Among these specialities, Periodontology is currently considered a formal dental speciality in 11 countries belonging to the EU however it lacks this legal status in the rest of the 14 EU countries. The purpose of this position paper is to provide evidence for the need for a recognized specialty in Periodontology at European level focusing on both the educational and professional perspective, with the hope of providing discussions that may contribute to facilitate its legal establishment as a new dental speciality in Europe.